Christianity and Transhumanism in the Inequity Era - Debates, Amy (Christian bioethics, 2025)
This paper explores the effects of increasing technological inequities through a theological lens, in relation to current advocacy by transhumanists, attending particularly to the impacts on minoritized people. Looking at both existing and emerging technologies, we can assess the multifaceted impacts that they have on human bodies and relationships in light of how they contribute to or deter human flourishing, particularly in light of Christian communities' responses to the COVID pandemic, with reflections from the perspective of a healthcare worker. Technologies for the human body are not inherently neutral and should be judged by their impact on the least privileged in global society.